2022
DOI: 10.1108/emjb-01-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Does board demographic diversity affect the dividend payout policy in Turkey?

Abstract: PurposeThe purpose of this study is to investigate the impact of board demographic diversity on the dividend payout policy in Turkish capital markets.Design/methodology/approachUsing a sample of 67 non-financial companies listed on Borsa Istanbul 100 index from 2013 to 2018, this study examines the influence of board demographic diversity on dividend payout policies in Turkish capital markets. The authors also create a Demographic Board Diversity Index (DBDI) to estimate the composite cognitive diversity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 85 publications
4
24
3
Order By: Relevance
“…In the dividend context, He et al (2016) explained that the chairman of the board with a business school educational background is less inclined to pay a dividend, although they are more risk averse and prefer sound business strategy, they may accept excessive investment behavior of managers for the sake of short-term stock price growth, or even accept managers to make the harmful decision to the shareholder. Contrary to that, Khan et al (2022) found a positive and significant relationship between BOD educational level and dividends. They convey ideas and solutions to problems that lead to more optimal resource management.…”
Section: Bod Education Level and Dividend Policycontrasting
confidence: 85%
See 4 more Smart Citations
“…In the dividend context, He et al (2016) explained that the chairman of the board with a business school educational background is less inclined to pay a dividend, although they are more risk averse and prefer sound business strategy, they may accept excessive investment behavior of managers for the sake of short-term stock price growth, or even accept managers to make the harmful decision to the shareholder. Contrary to that, Khan et al (2022) found a positive and significant relationship between BOD educational level and dividends. They convey ideas and solutions to problems that lead to more optimal resource management.…”
Section: Bod Education Level and Dividend Policycontrasting
confidence: 85%
“…Giannetti et al (2015) observed that they have unique resources that facilitate entry into international markets and transfer knowledge of management practices, resulting in soaring performance. They are also classified as having a more independent nature and willing to provide all ideas, commitments, and responsibilities only for the benefit of shareholders, thereby increasing performance and attracting new investors (Khan et al, 2022). In the context of dividends, Shehata (2021) documents that the presence of foreign nationals is deemed capable of paying attention to the interests of shareholders, as evidenced by the increase in dividend payments.…”
Section: Bod Nationality and Dividend Policymentioning
confidence: 99%
See 3 more Smart Citations